PENERAPAN GOOD GOVERNANCE PADA ORGANISASI PENGELOLA ZAKAT DALAM RANGKA OPTIMALISASI PENGGALANGAN DANA ZAKAT - Nasfizar Guspendri (JURIS (Jurnal Ilmiah Syariah), 2018)
Poverty and income gaps are crucial problems that Indonesian are still dealing with. Concerining with these problems, Islam has clearly offered divine tax (zakat) as one of possible solutions to solve problems of poverty. Such genuine function of zakat can be possible realized if it is managed well by related organization. This implies that good governance must be of priority concern in order that optimum and professional management of zakat can obtained.